CuxS/PAN 3D Nanofiber Mats as Ultra‐Lightweight and Flexible Electromagnetic Interference Shielding Materials. Issue 12 (9th October 2019) - Li, Heng; Jensen, Martin; Wang, Ning; Chen, Yang; Gao, Yaxue; Chen, Xueyan; Li, Xianfeng
Abstract: Shielding materials are becoming increasingly important, but present materials suffer from either insufficient mechanical stability or limited shielding properties. In this study, 3D flexible copper sulfide (Cu x S)/polyacrylonitrile (PAN) nanofiber mats are developed via air spinning followed by chemical reaction with copper salt. The Cu x S/PAN nanofiber mats exhibit an ultra‐lightweight density of 0.044 g cm −3 and a thickness of 0.423 mm. Stable electromagnetic interference (EMI) shielding effectiveness (SE) (29–31 dB) of the Cu x S/PAN composite is achieved in the frequency range of 500–3000 MHz. EMI SE per unit surface density of 16 655.92 dB cm 2 g −1 is several orders of magnitude higher than most copper sulfide containing EMI shielding materials reported in literature. In addition, the introduction of the Cu x S improves the thermal stability and launderability of the PAN mats giving the mats thermal, mechanical, and aqueous stability. Finally, the shielding mechanism of the Cu x S/PAN nanofiber mats for electromagnetic waves is proposed Abstract : 3D flexible Cu x S/PAN nanofiber mats are developed via air spinning followed by chemical reaction with copper salt, and they exhibit an ultra‐lightweight density of only 0.044 g cm −3 . Stable electromagnetic interference shielding effectiveness (29–31 dB) of the Cu x S/PAN composite is achieved in the frequency range of 500–3000 MHz.